3D-printing of shape-controllable thermoelectric devices with enhanced output performance. (15th March 2020) - Su, Ning; Zhu, Pengfei; Pan, Yuhui; Li, Fu; Li, Bo
Abstract: Reducing the heat loss between thermoelectric (TE) devices and heat sources is an important factor to improve the conversion efficiency of the devices. Direct-writing three-dimensional (3D) printing technology, which is a bottom-up additive manufacturing method, can produce complex structures that cannot be formed by traditional preparation methods and also has more flexibility in the design of structural parameters. In this work, TE materials consisting of Bi2 Te3 /polyvinylpyrrolidone (PVP) and Bi0.5 Sb1.5 Te3 /PVP composites with different contents of TE fillers and heat treatment times were synthesized by direct-writing 3D printing technology. The results showed that the sample containing 91 wt% TE filler displayed maximum figure of merit values of 0.104 (p-type) and 0.11 (n-type) after heat treatment for 6 h. The in-plane and annular TE devices were then printed by direct-writing technology and their output performance was measured. The annular device displayed an open-circuit voltage of 60.80 mV and maximum output power of 0.68 mW when the temperature difference was 54.6 K, which were consistent with the results obtained for simulations using the finite element method. Both the experimental and simulation results indicated that direct-writing 3D printing is an effective approach to fabricate TE materials and devices with excellent performance at room temperature. The shape-controllable TE devices can be applied to any shape of heat source to minimize heat loss. Highlights: TE composites and shape-controllable devices were fabricated by direct writing 3D printing technology. TE composites prepared by 3D printing technology displayed optimal ZT values of 0.104 (p-type) and 0.11 (n-type). The size of TE rings can be adjusted according to FEM results to further optimize the output performance of the annular devices.